2012
DOI: 10.1186/1756-3305-5-268
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Ixodes ricinus and prevalence of Borrelia burgdorferi s.l. in the nature reserve Siebengebirge, Germany, in comparison to three former studies from 1978 onwards

Abstract: BackgroundDuring the last decades, population densities of Ixodes ricinus and prevalences of Borrelia burgdorferi s.l. have increased in different regions in Europe. In the present study, we determined tick abundance and the prevalence of different Borrelia genospecies in ticks from three sites in the Siebengebirge, Germany, which were already examined in the years 1987, 1989, 2001 and 2003. Data from all investigations were compared.MethodsIn 2007 and 2008, host-seeking I. ricinus were collected by monthly bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 81 publications
1
25
2
Order By: Relevance
“…Sampling variation could contribute to a proportion of the observed variation, however the sample size of nymphs collected at each site ( n  = 200) was chosen to be high to minimize this. Variation in prevalence between years has also been reported at sites sampled over several years in Europe [71, 72] and North America [73], although a recent study in the Netherlands found surprisingly little inter-year variation at all sites [74]. …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sampling variation could contribute to a proportion of the observed variation, however the sample size of nymphs collected at each site ( n  = 200) was chosen to be high to minimize this. Variation in prevalence between years has also been reported at sites sampled over several years in Europe [71, 72] and North America [73], although a recent study in the Netherlands found surprisingly little inter-year variation at all sites [74]. …”
Section: Discussionmentioning
confidence: 92%
“…Another longitudinal study carried out in the Netherlands, in which B. afzelii was the dominant genospecies, found an alternating annual trend in prevalence at three out of four sites [71]. A decrease in B. afzelii prevalence between consecutive years was also noted at several sites in a study from Germany [72]. Rodent species are the most competent hosts for B. afzelii [16].…”
Section: Discussionmentioning
confidence: 99%
“…A number of field studies have already pointed to increases in average densities and activities of questing ticks in parts of Europe with long-documented I. ricinus populations (14,15). Moreover, the distributional area of I. ricinus appears to be steadily shifting toward higher altitudes and latitudes, increasing the total surface area of tick-suitable habitats in many European countries (16)(17)(18).…”
mentioning
confidence: 99%
“…In 2013, 834 ticks were collected in the Siebengebirge near Bonn at three neighboring locations typified by their plant community as described earlier [27]. In 2011 and 2012, 553 and 345 I. ricinus, respectively, were collected in the English Garden, Munich, and in 2012 additional 331 in Grafrath, Fürstenfeldbruck, and 60 near Schloss Lustheim, Oberschleißheim, Bavaria.…”
Section: Origin Of Ticksmentioning
confidence: 99%
“…2123 ticks were collected in different regions in Germany and 218 in Slovakia by blanket dragging using a cotton flannel [13,27]. In 2013, 834 ticks were collected in the Siebengebirge near Bonn at three neighboring locations typified by their plant community as described earlier [27].…”
Section: Origin Of Ticksmentioning
confidence: 99%